Cellulose-Based Pickering Emulsion-Templated Edible Oleofoam: A Novel Approach to Healthier Solid-Fat Replacers - Sang Min Lee; Su Jung Hong; Gye Hwa Shin; Jun Tae Kim (Gels, 2025)
As health concerns and regulatory pressures over saturated and trans fats grow, there is a growing need for healthier alternatives to traditional solid fats, such as butter and hydrogenated oils, that are still widely used in the food system. In this study, cellulose particle-based Pickering emulsions (CP-PEs) were prepared from microcrystalline cellulose and ethylcellulose and then foamed to obtain edible oleofoams (CP-EOs) as a solid-fat replacer. The average size of CP-PE droplets without surfactant was 598 ± 69 nm, as confirmed by confocal and transmission electron microscopy. Foaming with citric acid/NaHCO3 and structuring with ≥6% glyceryl monostearate resulted in CP-EOs with an overrun of 147 ± 4% and volumetric stability for 72 h. Micro-computed tomography showed a uniform microcellular network, while the rheological analysis showed solid-like behavior with a storage modulus higher than butter. Differential scanning calorimetry showed a melting enthalpy similar to unsalted butter (10.1 ± 0.9 J/g). These physicochemical properties demonstrate that CP-EOs can closely mimic the firmness, thermal profile, and mouth-feel of conventional solid fats and may provide a promising solid-fat replacer.